PENGARUH KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS KELAUTAN DAN PERIKANAN KOTA SEMARANG - Balawan Tri Atmaja, 10.05.51.0088; Murdiyanto, Agus (Students Journal of Economic and Management, 2014)
This study aims to analyze the influence of Leadership, Motivation and Work Environment on Employee Performance Department of Marine and Fisheries Semarang City. The population in this study is the total number of employees amounted to 55 respondents. The data used are primary data, that is data obtained directly from the source. The technique used for primary data collection is done by means of questionnaires to the respondents. The test of determination (RÂ²) indicate that employee performance can be explained by Leadership, Motivation and Work Environment of 85%, while the remaining is influenced by other variables outside of research. The f test indicate that Leadership, Motivation and Work Environment jointly significant effect on employee performance. The t test indicate that leadership has a positive and significant impact on employee performance, motivation has a positive and significant impact on employee performance, work environment has a positive and significant impact on employee performance.Keywords: Leadership, Motivation, Workplace Environment and Employee Performance.